Capacity Building for Teachers and Students in Understanding the Concept of Morphological Characters of Honey Bees from Maluku and their Cultivation Technology - Mercy Papilaya, Pamela; SA Lamerkabel, Jacobus; MJ Tuapattinaya, Prelly (Pascasarjana Universitas Mataram, 2025)
Science learning, which is often theoretical at SMP Negeri 14 Ambon, is less connected to local biological potential. As a result, teachers and students' understanding of honey bees native to Maluku, both from the morphological aspect to the cultivation technology, is still limited. This service activity aims to increase the capacity of teachers and students on the topic as contextualized science enrichment material. The methods used include counseling, training, and hands-on demonstrations on morphological characters and bee cultivation technology. The results showed a significant increase in participants' enthusiasm and understanding. Teachers obtained new relevant teaching materials, while students were able to connect biology concepts with practical applications. Thus, this pengabdin activity was carried out to integrate local content and increase the relevance of science learning.